STRUCTURE OF fac-[(ppyEt)Re(CO)3Br], A MONONUCLEAR ReI COMPLEX DERIVED FROM PYRROLINE-PYRAZOLYL-PYRIDAZINE - Vega, Andres; Pizarro, Nancy; Saldías, Marianela; Palominos, Franco (Journal of the Chilean Chemical Society, 2020)
The reaction of 6-(1H-3,5-dimethylpyrazolyl)pyridazine-3-carboxylic acid with oxalyl chloride and then 2,4-dimethyl-3-ethylpyrrole leads to [6-(3,5-dimethyl-1H-pyrazol-1-yl)pyridazin-3-yl](4-ethyl-3,5-dimethyl-1H-pyrrol-2-yl)methanone (ppyEt). The reaction of ppyEt with bromotricarbonyl(tetrahydrofuran)-rhenium(I) dimer leads to [(ppyEt)Re(CO)3Br] compound. The molecule of [(ppyEt)Re(CO)3Br] displays a non-regular octahedron around the rhenium(I) center with a bromide. The molecule defines an intramolecular hydrogen bond between the 4-ethyl-3,5-dimethyl-1H-pyrrol-2-yl hydrogen atom and one nitrogen from the pyridazin-3-yl fragment with D···A 2.833(17) Å. The coplanarity of the 4-ethyl-3,5-dimethyl-1H-pyrrol-2-yl-carbonyl is attributed to this intramolecular bond, in addition to C—H···O≡C and N—H···O≡C interactions as suggested by NCI calculations.